Threat, voting and candidate support. The impact of mortality salience - Bäck, Hanna; Carroll, Royce; Knapton, Holly; Renström, Emma A. (Frontiers in Political Science, 2023)
Introduction How does threat motivate political choices? An extensive literature has noted the importance of threat in influencing political behavior. A growing literature in political psychology has used the concept of “mortality salience” to examine the role of existential threat in political decisions. Scholars have argued that inducing mortality salience by asking individuals to think about their own death should result in either reinforcement of their existing political worldview, a shift to a more politically conservative view, or support for a “status quo” option more generally. Methods We performed two survey experiments (N = 484 and 1514) manipulating mortality salience and candidate features (Exp. 2). Experiment 1 was performed one week before the 2016 US presidential election and utilized the varying features of the candidates. Experiment 2 manipulated features such as experience level (representing the status quo or change) and partisanship. Results We find that mortality salience led to an increased likelihood of voting for Hillary Clinton, particularly for moderate and independent respondents. We also find that independent participants preferred the status quo candidate under mortality salience. Discussion We interpret the findings in both studies as supporting a connection between existential threat and preference for the status quo in psychological terms, at least for less partisan voters, rather than a conservative shift in ideological terms or a tendency to reinforce existing views.